2016
DOI: 10.1089/vbz.2015.1911
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Introductions of Dengue 2 Virus Strains into Saudi Arabia from 1992 to 2014

Abstract: The close clustering of DENV-2 isolates reported from Saudi Arabia between 1992 and 2014 with strains from countries providing the highest numbers of pilgrims attending either Hajj or Umrah pilgrimages (Indonesia, Pakistan, India) clearly suggests a role for pilgrims or expatriates coming from DENV endemic countries in DENV-2 importation into Saudi Arabia. Accordingly, continuous monitoring of the circulation of DENVs in Saudi Arabia must be implemented to undertake effective control and management strategies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 30 publications
(48 reference statements)
4
25
0
Order By: Relevance
“…Interestingly, this study is also the first to report DENV-4 in KSA and the rate of detecting this serotype was similar to those of DENV-2, which is the most prevalent serotype in Jeddah and Makkah cities [4, 6, 10, 12, 25, 26]. Moreover, DENV-4 was the only detected serotype among those individuals who were exclusively positive for IgM antibodies.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Interestingly, this study is also the first to report DENV-4 in KSA and the rate of detecting this serotype was similar to those of DENV-2, which is the most prevalent serotype in Jeddah and Makkah cities [4, 6, 10, 12, 25, 26]. Moreover, DENV-4 was the only detected serotype among those individuals who were exclusively positive for IgM antibodies.…”
Section: Discussionsupporting
confidence: 72%
“…In this context, several studies have shown independent multiple introductions of DENV-1 (lineage India-2 and lineage Asia-2) and DENV-2 (Cosmopolitan genotype and DENV-2-Jeddah-2014) in the Western province of the kingdom between the years 1994 and 2014 [10, 11, 25]. Additionally, the most recent report by the United Nations has estimated that 10 million migrant workers are living in KSA and many of them are from India and Pakistan where DENV-4 is endemic [28–30].…”
Section: Discussionmentioning
confidence: 99%
“…In Saudi Arabia, at least five vector‐borne flaviviruses are circulating including DENV‐1, DENV‐2, DENV‐3, DENV‐4, and AHFV in addition to two other arboviruses (Rift Valley fever virus [RVFV] and Crimean‐Congo haemorrhagic fever virus [CCHF]) . These viruses are known to be endemic and causing outbreaks or sporadic infections in several regions in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…Cities such as Jeddah, Makkah, and Al‐madinah in western Saudi Arabia are endemic for DENV and AHFV, and represent a major destination for pilgrims coming for annual Hajj and/or Umrah pilgrimages from all over the world. This clearly poses a great concern about the possible introduction of new viruses into the Kingdom [Azhar et al, 2016] . Although there have been no reports of Zika infection in Saudi up to now, the current outbreak in South and Central America as well as the heavy travel to Saudi from all over the world may put the Kingdom at the front‐line in the fight against ZIKAV particularly with the high prevalence of Aedes aegypti which is the vector for both Zika and dengue viruses .…”
Section: Introductionmentioning
confidence: 99%
“…Aedes aegypti is a formidable vector: its high vectorial capacity (the ability of a vector species to transmit a pathogen in a specific location at a specific time) lies in its ability to feed predominantly on human beings, bite almost imperceptibly and feed on multiple humans in a single blood meal, transmitting the virus as it goes (7,8). It also lives in close proximity to human habitation being found both external to and inside impacted dwellings.…”
Section: Zika Virus and Saudi Arabiamentioning
confidence: 99%